2021
DOI: 10.1007/s10639-021-10494-3
|View full text |Cite
|
Sign up to set email alerts
|

The symbiotic relationship between educational robotics and computer science in formal education

Abstract: Educational Robotics (ER) has the potential to provide significant benefits to education, provided an increase in outreach by transitioning from the extra-curricular initiatives in which ER has thrived to formal education. As Computer Science (CS) Education is undergoing curricular reforms worldwide, the present study addresses the case of a Digital Education reform that included ER as a means to teach core CS concepts. Approximately 350 teachers from the first four grades of primary school participated in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…The case studies reported in this article are based on two popular CSU activities [3] for grades 1-4 (ages 5-9) from our regional CS curricular reform [16,17]: the robot game [40] and the sorting machine [2].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The case studies reported in this article are based on two popular CSU activities [3] for grades 1-4 (ages 5-9) from our regional CS curricular reform [16,17]: the robot game [40] and the sorting machine [2].…”
Section: Methodsmentioning
confidence: 99%
“…Each case study involved one grade 3 and one grade 4 class (students aged 7-9) and their respective in-service teachers with a researcher present to observe the sessions. The teachers that participated in the studies had completed the mandatory regional CS continuing professional development program headed by the department of education the previous year [16,17]. This involved 4 days of CS-related teacher training which targeted concepts of algorithms & programming, machines & networks, and information & data.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations